2001
DOI: 10.7589/0090-3558-37.4.711
|View full text |Cite
|
Sign up to set email alerts
|

Concentrations and Interactions of Selected Essential and Non-Essential Elements in Ringed Seals and Polar Bears of Arctic Alaska

Abstract: In this study, we evaluated concentrations of twelve essential and non-essential elements (As, Cd, Co, Cu, Pb, Mg, Mn, Hg, Mo, Se, Ag, and Zn) in tissues of ringed seals (Phoca hispida) and polar bears (Ursus maritimus) of arctic Alaska (USA). All samples were collected between 1995-97 in conjunction with subsistence harvests. The essential elements are reported to help develop reference ranges for health status determination and to help assess known or suspected interactions affecting toxicoses of cadmium (Cd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
38
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(47 citation statements)
references
References 30 publications
7
38
1
Order By: Relevance
“…However, Hg concentrations in bowheads are relatively miniscule compared to other marine mammals, and are below levels used by regulatory agencies for marketed animal products. Compared to other species of northern Alaska, bowhead whales of this study had similar or lower tissue concentrations of the toxic metal Hg (17,18). The Cd concentrations are similar to those previously reported for bowhead whales (18,27), which accumulate Cd with age in liver, and particularly in kidney (18), similar to other arctic mammals, including both terrestrial and marine species (17,18,32,33,34,35,36,37,38,39).…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…However, Hg concentrations in bowheads are relatively miniscule compared to other marine mammals, and are below levels used by regulatory agencies for marketed animal products. Compared to other species of northern Alaska, bowhead whales of this study had similar or lower tissue concentrations of the toxic metal Hg (17,18). The Cd concentrations are similar to those previously reported for bowhead whales (18,27), which accumulate Cd with age in liver, and particularly in kidney (18), similar to other arctic mammals, including both terrestrial and marine species (17,18,32,33,34,35,36,37,38,39).…”
Section: Discussionsupporting
confidence: 71%
“…Compared to other species of northern Alaska, bowhead whales of this study had similar or lower tissue concentrations of the toxic metal Hg (17,18). The Cd concentrations are similar to those previously reported for bowhead whales (18,27), which accumulate Cd with age in liver, and particularly in kidney (18), similar to other arctic mammals, including both terrestrial and marine species (17,18,32,33,34,35,36,37,38,39). Other reports have addressed potential nutritional and toxic effects of such elemental concentrations in bowhead whales and domestic animals (32,18).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…This complex probably represents a direct covalent (or other strong) interaction of Hg and Se. In some wild aquatic predatory bird and mammal species, it has been shown that MeHg predominates in the liver at low total Hg (THg) concentrations whereas at higher concentrations an increasingly large percentage of THg is present as inorganic Hg associated with Se, and some studies have identified this complex as HgSe (tiemanite) (Koeman and van deVen, 1975;Dietz et al, 1990Dietz et al, , 1998aDietz et al, , 1998bDietz et al, , 2000aDietz et al, 2000bScheuhammer et al, 1998Scheuhammer et al, , 2008Wang et al, 2001;Woshner et al, 2001aWoshner et al, , 2001bWoshner et al, , 2008O'Hara et al, 2003;Arai et al, 2004;Ikemoto et al, 2005;Dehn et al, 2005Dehn et al, , 2006Eagles-Smith et al, 2009;Moses et al, 2009;Routti et al, 2011).…”
Section: Mercury-selenium Relationships and Interactionsmentioning
confidence: 99%
“…Among studies that do examine mercury levels in non-laboratory animals, many have examined exposures of wild and domestic animals to mercury that could serve as sentinels for human exposure [8][9][10]. Animals including wild mink [9], vampire bats [10], hares and rabbits [11], wild seals and bears [12], wild birds [13], domestic cattle and domestic fowl [14][15][16], and domestic dogs [17] are some of the animals that have been assessed for their mercury "body load" over the past 20 to 25 years.…”
mentioning
confidence: 99%